Effect of aqueous extract of Tinospora cordifolia on functions of peritoneal macrophages isolated from CCl4 intoxicated male albino mice - Sharma Gauri D; Sengupta Mahuya; Chakraborty Biswajit (BMC, 2011)
Abstract Background The current practice of ingesting phytochemicals for supporting the immune system or fighting infections is based on centuries-old tradition. Macrophages are involved at all the stages of an immune response. The present study focuses on the immunostimulant properties of Tinospora cordifolia extract that are exerted on circulating macrophages isolated from CCl4 (0.5 ml/kg body weight) intoxicated male albino mice. Methods Apart from damaging the liver system, carbon tetrachloride also inhibits macrophage functions thus, creating an immunocompromised state, as is evident from the present study. Such cell functions include cell morphology, adhesion property, phagocytosis, enzyme release (myeloperoxidase or MPO), nitric oxide (NO) release, intracellular survival of ingested bacteria and DNA fragmentation in peritoneal macrophages isolated from these immunocompromised mice. T. cordifolia extract was tested for acute toxicity at the given dose (150 mg/kg body weight) by lactate dehydrogenase (LDH) assay. Results The number of morphologically altered macrophages was increased in mice exposed to CCl4. Administration of CCl4 (i.p.) also reduced the phagocytosis, cell adhesion, MPO release, NO release properties of circulating macrophages of mice. The DNA fragmentation of peritoneal macrophages was observed to be higher in CCl4 intoxicated mice. The bacterial killing capacity of peritoneal macrophages was also adversely affected by CCl4. However oral administration of aqueous fraction of Tinospora cordifolia stem parts at a dose of 40 mg/kg body weight (in vivo) in CCl4 exposed mice ameliorated the effect of CCl4, as the percentage of morphologically altered macrophages, phagocytosis activity, cell adhesion, MPO release, NO release, DNA fragmentation and intracellular killing capacity of CCl4 intoxicated peritoneal macrophages came closer to those of the control group. No acute toxicity was identified in oral administration of the aqueous extract of Tinospora cordifolia at a dose of 150 mg/kg body weight. Conclusion From our findings it can be suggested that, polar fractions of Tinospora cordifolia stem parts contain major bioactive compounds, which directly act on peritoneal macrophages and have been found to boost the non-specific host defenses of the immune system. However, the molecular mechanism of this activity of Tinospora cordifolia on immune functions needs to be elucidated.